2009
DOI: 10.1098/rsif.2009.0221
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the analysis of behavioural organization and interpretation as indicators of animal welfare

Abstract: While the incorporation of mathematical and engineering methods has greatly advanced in other areas of the life sciences, they have been under-utilized in the field of animal welfare. Exceptions are beginning to emerge and share a common motivation to quantify 'hidden' aspects in the structure of the behaviour of an individual, or group of animals. Such analyses have the potential to quantify behavioural markers of pain and stress and quantify abnormal behaviour objectively. This review seeks to explore the sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
92
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(95 citation statements)
references
References 147 publications
0
92
0
1
Order By: Relevance
“…This value was then subtracted from 1, yielding the probability that data are sequentially dependent, and logit transformed to make its distribution unbounded. (2) Detrended Fluctuation Analysis: DFA is a fractal method of analyzing selfsimilarity in sequential binary data, recommended for ethological analyses of sequential behaviour [65,66]. DFA yields a single alpha score for each mink's response sequence, which equals 0.50 for random data sequences and increases with sequential dependency.…”
Section: Testing For Recurrent Perseverationmentioning
confidence: 99%
“…This value was then subtracted from 1, yielding the probability that data are sequentially dependent, and logit transformed to make its distribution unbounded. (2) Detrended Fluctuation Analysis: DFA is a fractal method of analyzing selfsimilarity in sequential binary data, recommended for ethological analyses of sequential behaviour [65,66]. DFA yields a single alpha score for each mink's response sequence, which equals 0.50 for random data sequences and increases with sequential dependency.…”
Section: Testing For Recurrent Perseverationmentioning
confidence: 99%
“…DFA was introduced by Peng et al (1992) to identify long-range dependence in nucleotide sequences and has since become the method of choice for researchers studying fractal dynamics in a diverse array of systems ranging from temperature to heart rate to animal behaviour , Rutherford et al 2004, Király & Jánosi 2005, Asher et al 2009). The scaling exponent calculated via DFA (αDFA) provides a relatively robust estimate of the Hurst exponent, which measures the degree to which time series are long-range dependent and statistically self-similar or self-affine (Taqqu et al 1995, Cannon et al 1997.…”
Section: Diving Data Analysismentioning
confidence: 99%
“…Altered complexity signatures may reflect changes toward either greater stereotypy or greater randomness, depending on the nature of the disruption [17,18,26]. Kembro et al [31] for instance showed increased stochasticity in the movement behavior of mosquito larvae exposed to lethal and sub-lethal doses of essential oils.…”
Section: Introductionmentioning
confidence: 99%
“…Fractal time series analyses of animal behavior measure the structure of behavior as it occurs through time, which is linked to the concept of behavioral organization [17,19]. Borrowing from the field of complexity science, such studies have adopted the term 'complexity' to refer to the correlation structure of the time series, which behave as nonlinear systems [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation